"I think maybe 10 years seems a bit long." Beliefs and attitudes of women who had never used intrauterine contraception. Issue 2 (22nd January 2018) - Walker, Susan; Newton, Victoria Louise; Hoggart, Lesley; Parker, Michael
Abstract : Aim: To explore, in a general practice setting, the concerns, beliefs and attitudes about intrauterine contraception (IUC) reported by women, who had never used the methods. Methods: We used a sequential mixed-method (QUAL/quant) approach. A pragmatic, self-selecting sample of 30 women, aged 18–46 years, who had never used IUC), was recruited through seven general practices in South East England. Themes arising from qualitative interviews were used to construct a quantitative survey, completed by a pragmatic sample of 1195 women, aged 18–49 years, attending 32 general practices in the same region, between February and August 2015. Results: Qualitative themes were concerns about the long-acting nature of IUC, concerns about body boundaries, and informal knowledge of IUC, especially 'friend of a friend' stories. Women were not sure if the devices can be removed before their full 5- or 10-year duration of use, and felt that these timeframes did not fit with their reproductive intentions. Quantitative survey data showed that the most commonly endorsed concerns among never-users were painful fitting (55.8%), unpleasant removal of the device (60.1%), and concern about having a device 'inside me' (60.2%). Conclusions: To facilitate fully informed contraceptive choice, information provided to women considering IUC should be tailored to more fully address the concerns expressed by never-users, particularly around the details of insertion and removal, and concerns about the adverse, long-term effects of the device. Women need to be reassured that IUC can be removed and fertility restored at any time following insertion. Trial registration: Trial registration NIHR CRN portfolio; 15912.